RNAi revised - target mRNA-dependent enhancement of gene silencing. Issue 22 (17th November 2015) - Dornseifer, Simon; Willkomm, Sarah; Far, Rosel Kretschmer-Kazemi; Liebschwager, Janine; Beltsiou, Foteini; Frank, Kirsten; Laufer, Sandra D.; Martinetz, Thomas; Sczakiel, Georg; Claussen, Jens Christian; Restle, Tobias
Abstract: The discovery of RNA interference (RNAi) gave rise to the development of new nucleic acid-based technologies as powerful investigational tools and potential therapeutics. Mechanistic key details of RNAi in humans need to be deciphered yet, before such approaches take root in biomedicine and molecular therapy. We developed and validated an in silico- based model of siRNA-mediated RNAi in human cells in order to link in vitro- derived pre-steady state kinetic data with a quantitative and time-resolved understanding of RNAi on the cellular level. The observation that product release by Argonaute 2 is accelerated in the presence of an excess of target RNA in vitro inspired us to suggest an associative mechanism for the RNA slicer reaction where incoming target mRNAs actively promote dissociation of cleaved mRNA fragments. This novel associative model is compatible with high multiple turnover rates of RNAi-based gene silencing in living cells and accounts for target mRNA concentration-dependent enhancement of the RNAi machinery.